Envolvimento do receptor de potencial transitório A1 (TRPA1) em um modelo de dor neuropática mantida pelo simpático em camundongos - Pinheiro, Francielle de Vargas (2012)
Some forms of neuropathic pain are maintained by sympathetic fibers, but the underlying mechanisms are poorly understood. Thus, the aim of this study was to investigate the possible involvement of the TRPA1 receptor as well as the role of the sympathetic nervous system (involved in sympathetically maintained neuropathic pain) in a model of neuropathic pain induced by chronic sciatic nerve constriction injury (CCI) in mice. The systemic injection of the selective TRPA1 antagonist HC-030031 reversed both mechanical and cold allodynia induced by chronic sciatic nerve constriction injury. Nerve injury also sensitizes mice to the nociception induced by the intraplantar injection of a low dose of the TRPA1 agonist allyl isothiocyanate without changing TRPA1 immunoreactivity in the injected paw. Furthermore, the chemical sympathectomy produced by guanethidine largely prevented CCI-induced mechanical and cold allodynia. CCI also induced a norepinephrine-trigged nociception that was inhibited by α-adrenoceptor antagonism and norepinephrine transporter and monoamine oxidase inhibition. Finally, the peripheral injection of HC-030031 also largely reduced CCI-induced nociception by norepinephrine and mechanical or cold allodynia. Taken together, the present findings reveal the critical role of TRPA1 in mechanical and cold hypersensitivity as well as in hypersensitivity to norepinephrine following nerve injury. This article presents the role of TRPA1 receptor on the sympathetically-maintained nociception induced by nerve injury in mice. Our results suggest that TRPA1 antagonists may be useful to treat neuropathic patients that present sympathetically maintained pain.